2014
DOI: 10.2147/opth.s61682
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric glaucoma suspects

Abstract: PurposeTo report demographic and ocular features of pediatric glaucoma suspects in an ethnically diverse population of North Central Texas.DesignRetrospective cross-sectional chart review.ParticipantsSubjects included 75 (136 eyes) pediatric glaucoma suspects. Patients with one or more of the following risk factors were included: cup-to disc (C/D) ratio of ≥0.6; intraocular pressure (IOP) ≥21 mmHg; family history of glaucoma; congenital glaucoma in the opposite eye; history of blunt trauma to either eye; and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Leukocoria or corneal haze were the leading presenting symptom in PCG (46.9%) and SCG-O (77%) similar with previous studies [16][17][18] . Moreover, most patients with JOAG were diagnosed without any symptoms.…”
Section: Conclusion/discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Leukocoria or corneal haze were the leading presenting symptom in PCG (46.9%) and SCG-O (77%) similar with previous studies [16][17][18] . Moreover, most patients with JOAG were diagnosed without any symptoms.…”
Section: Conclusion/discussionsupporting
confidence: 89%
“…High IOP was the leading clue for glaucoma diagnosis. Furthermore, an enlarged corneal diameter was considered an important sign of PCG 16 .…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…[ 14 ] Regular accurate assessment and long term follow up is very much essential in patients with high risk factors like suspicious optic discs, cup-to disc (C/D) ratio of ≥0.6, asymmetry more than 0.2 between the two eyes, narrow neuroretinal rim, persistently elevated IOP of ≥21 mmHg, family history of glaucoma in the parents or sibling, diagnosis of congenital glaucoma in the other eye, history of blunt trauma to either eye and conditions associated with glaucoma such as Sturge-Weber syndrome or Axenfeld-Rieger syndrome. [ 15 ] In the current study, measured IOP value is found to vary with the depth of anesthesia. Therefore, accurate IOP assessment under targeted optimum depth of anesthesia with BIS monitoring can be justified in certain selected high-risk population, where management depends on the accuracy of measured IOP.…”
Section: Discussionmentioning
confidence: 63%
“…However, as mentioned above, few studies have investigated IOP in children, while research has been mainly focused on the adult population, albeit with contrasting findings [4-6]. Studies performed in children were designed and conducted with varying methodologies with regard to children’s eye diseases, mainly conducted in patients with suspected pediatric glaucoma [32], or in hospitalized children who had undergone ocular surgery [33]. Among studies performed in the healthy population, the role of BP was erratically recognized.…”
Section: Discussionmentioning
confidence: 99%